2013
DOI: 10.4236/health.2013.56130
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study evaluating the factors associated with psychological distress of school teachers in Kagawa Prefecture, Japan

Abstract: Objective: We investigated the psychological distress of school teachers using a 6-item instrument (the K6) in Kagawa prefecture, Japan. Methods: A total of 670 school teachers (328 men and 342 women) were analyzed in this crosssectional investigation study. The association between psychological distress and clinical factors was evaluated by using the K6 instrument, with psychological distress defined as 13 or more points out of a total of 24 points. Results: A total of 55 teachers (8.2%) were classified as ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
2
2
1
Order By: Relevance
“…According to psychological distress in clinical psychologists, the percentage of clinical psychologists with high psychological distress was similar to that of the general Japanese population (Kuriyama et al, 2009), and was lower than that of school teachers (Miyamae et al, 2013) and employees (Fushimi et al, 2012). Psychological distress in clinical psychologists in this study was not very high and this result agreed with that reported by Rupert et al (Rupert & Kent, 2007;Rupert & Morgan, 2005).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…According to psychological distress in clinical psychologists, the percentage of clinical psychologists with high psychological distress was similar to that of the general Japanese population (Kuriyama et al, 2009), and was lower than that of school teachers (Miyamae et al, 2013) and employees (Fushimi et al, 2012). Psychological distress in clinical psychologists in this study was not very high and this result agreed with that reported by Rupert et al (Rupert & Kent, 2007;Rupert & Morgan, 2005).…”
Section: Discussionsupporting
confidence: 85%
“…As previously shown (Miyamae et al, 2013;Sakano et al, 2012;Suzue et al, 2011), the questionnaires for clinical psychologists consisted of the following details in sequence: sex, age, duration of experience as a clinical psychologist, classi cation of clinical eld (Japanese Society of Certi ed Psychologists, 2009), (Medical, health, welfare eld/Educational eld/University, research institution/Justice, legal, police eld/Industry, labor eld/Private practice), and other certi cations (Japanese Society of Certi ed Psychologists, 2009), (Physician/Nurse/Certi ed social worker, psychiatric social worker/Speech therapist/ Teacher/Other). In addition, we evaluated the consciousness of suicide among clients (Miyamae et al, 2013;Sakano et al, 2012;Suzue et al, 2011), anxiety about preventing suicide (Miyamae et al, 2013;Sakano et al, 2012;Suzue et al, 2011), and frequency of receiving supervision (Japanese Society of Certi ed Psychologists, 2009), and participating in a case study by asking the following questions: 1) Do you ever worry about suicide of clients in your daily work as a clinical psychologist? (most of the time/some of the time/a little of the time/none of the time) 2) If you had to do something individually to prevent the suicide of a client (clients) in your daily work as a clinical psychologist, how much anxiety would you feel?…”
Section: Methodssupporting
confidence: 61%
See 1 more Smart Citation
“…One study in Japan used the K6 to investigate psychological distress among school teachers in 2010-2011. 27 At that time, a total of 55 teachers (8.2%) were classified as having psychological distress, which was lower than the 12% reported among this study's participants during the COVID-19 pandemic. Unlike this study, the Japanese study was not conducted during the pandemic in 2010-2011.…”
Section: Discussioncontrasting
confidence: 66%
“…Using the K6 questionnaire, we have previously evaluated psychological distress of public health nurses [15], school teachers [16], and medical doctors [17] in Kagawa Prefecture, Japan, in a cross-sectional study, and 5.9, 8.2, BMI body mass index (kg/m 2 ), SBP systolic blood pressure (mmHg), DBP diastolic blood pressure (mmHg) and 6.0 %, respectively, were defined as having psychological distress [15][16][17]. In community dwelling Japanese, the prevalence of psychological distress has been reported to be 6.7 % [18].…”
Section: Discussionmentioning
confidence: 99%